Monte Carlo simulation of polarization of light back-scattered from randomly rough surfaces - Jiang, Yuxiang; Li, Zhenhua (Oficyna Wydawnicza Politechniki Wrocławskiej, 2023)
Laser detection devices obtain target information from back-scattered light, such as lidar. The recognition rate can be improved by analyzing intensity and polarization of echo signal. In this paper, Monte Carlo method is used to generate a large number of randomly rough surfaces to simulate targets. Every rough surface is discretized into a large number of micro-surface elements. Stokes parameters of back-scattered light are calculated by numerical integration. Incident light is p-, s-, 45° linearly polarized light and right-hand circularly polarized light, respectively. Numerical results show that when s- and p-linearly polarized light incident on a metal rough surface, back-scattered light appears circularly polarized component. Metal rough surface resembles a wave plate with phase difference, with the fast axis parallel or perpendicular to the 45° direction. When linearly polarized light is incident on dielectric rough surface, back-scattered light has no circularly polarized component. Experimental data are consistent with the numerical results. The above research provides a new basis for laser detection device to identify metal targets from the environmental background.
Optica Applicata, Vol. 53, 2023, nr 1, s. 65-85
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; back scattering; randomly rough surface; Stokes parameters; Monte Carlo method; polarized light